Endangered Plants - Kumar, Sanjeet (IntechOpen, 2021)
This book presents a multitude of contemporary views on endangered plants. Section I discusses a variety of endangered species and Section II presents conservation strategies for these plants. Chapters emphasize the impacts of climate change and anthropogenic activities on endangered plants and their restoration. It also explores recent developments in sustainable methods of conservation.